A phase II study of preoperative mFOLFOX6 with short-course radiotherapy in patients with locally advanced rectal cancer and liver-only metastasis. Issue 2 (February 2016) - Kim, Kyung Hwan; Shin, Sang Joon; Cho, Min Soo; Ahn, Joong Bae; Jung, Minkyu; Kim, Tae Il; Park, Young Suk; Kim, Hoguen; Kim, Nam Kyu; Koom, Woong Sub
Abstract: Background and purpose: To evaluate the efficacy and safety of upfront mFOLFOX6 followed by short-course radiotherapy (SCRT) and surgery in patients with locally advanced rectal cancer and liver-only metastases. Materials and methods: This single-arm phase II study involved 32 patients. mFOLFOX6 was administered for four cycles followed by SCRT and another four cycles of mFOLFOX6. Surgery was performed 4–6 weeks after the last chemotherapy cycle. The primary endpoint was complete (R0) resection rate. Secondary endpoints were response rate, progression-free survival (PFS), overall survival (OS), and complication rates. Results: Surgical resection of the rectum and liver was performed in 25 patients (78%) and R0 resection was achieved in 20 patients (63%). Local tumor downstaging was observed in 54% of patients. Median OS and PFS were 38 and 9 months, respectively. One patient discontinued treatment due to toxicity and no treatment-related deaths occurred. Patients who progressed after 4 cycles of mFOLFOX6 were less likely to receive resection. Conclusions: This regimen was safe and effective in inducing local tumor response and achieving R0 resection in this patient population.